Interannual Variability of the Indonesian Throughflow in the Makassar Strait Associated With the 2015/2016 Super El Niño - Wending Xu; Dongliang Yuan; Mingting Li (Geophysical Research Letters)
Abstract The interannual variability of the Indonesian Throughflow (ITF) in the Makassar Strait in 2015–2017 is analyzed using observations and ORAS5 reanalysis data. Strong northward and ensuing strong southward current anomalies in the sub‐thermocline Makassar Strait are identified during and after the 2015/2016 El Niño, respectively. However, the upper layer current anomalies are weakly southward in September–October 2015 and strongly northward in April 2016 through April 2017. These anomalies of the Makassar Strait throughflow in the upper layer are found to be induced mainly by Indian Ocean Kelvin waves forcing sea surface height anomalies off the south Java coasts. The sub‐thermocline current anomalies are found to be generated by the westward and downward propagation of interannual Rossby waves from the central equatorial Pacific during and after the 2015/2016 El Niño. The results underline the importance of the planetary wave propagation into the Indonesian seas in forcing the ITF anomalies.